EVALUASI TERHADAP TIPE KEPEMIMPINAN DALAM PENEGAKKAN DISIPLIN KARYAWAN PADA PT. PUTRA DARMA CEMERLANG PALEMBANG - Ahmad Yani Kosali (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
Leadership is a controlling tool in the organization that there is a relationship between followers because it is influenced by the authority of the leader. Employees become obedient to leaders because of the leader’s authority. The leader is a person who has technical skills. Especially in one field. So that leader can influence and control others to jointly carry out activities that are included in the organizational plan framework. Leadership generally is supported by strong motivation from oneself. In Principle the level of success in carrying out the task is determined by the ability of the leaders in fostering, guiding, building and motivating employees to complete work on time, smart, Skilled and full of responsibility. Therefore the leader is very instrumental in creating good cooperation to carry out company activities and establish good communication with employees.